2011
DOI: 10.1016/j.ajpath.2010.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for Giant Cell Tumor of Bone Using Comparative Proteomics Analysis

Abstract: Giant cell tumor of bone can be locally aggressive and occasionally can metastasize in the lungs. To identify new markers predictive of aggressive behavior, we analyzed five patients who developed lung metastasis and five who remained disease free for a minimum of 5 years. Using two-dimensional electrophoresis, we detected 28 differentially expressed spots. Fourteen spots were identified using mass spectrometry, including seven up-regulated and seven down-regulated in metastatic samples and classified accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…New proteins have been identified that are involved in tumor cell survival and are associated with increased aggressiveness of GCTs that leads, in most cases, to local recurrences and, more rarely, to metastasis (Conti et al, 2011). PTHrP excreted by GCT stromal cells increases bone tumor cell local invasiveness and migration (Mak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New proteins have been identified that are involved in tumor cell survival and are associated with increased aggressiveness of GCTs that leads, in most cases, to local recurrences and, more rarely, to metastasis (Conti et al, 2011). PTHrP excreted by GCT stromal cells increases bone tumor cell local invasiveness and migration (Mak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the tumor pattern is formed by a network of multinucleated osteoclastlike giant cells, spindle-shaped fibroblast-like stromal cells, round mononuclear histiocytic cells, and CD68-positive phagocytic histiocytes (Werner, 2006). A few proteomics analysis studies have been reported (Conti et al, 2011;Zhang et al, 2013). However, the use of isobaric tags for relative and absolute quantitation (iTRAQ) technology to identify the differentially expressed proteins associated with GCT has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…The process of the identification of Hsp70 was carried out by the use of a comparative proteinanalysis [22]. Identification of Hsp70 expression was carried out in this study because these proteins related to natural history of most tumor and might be the target of therapy in the future [23] [24].…”
Section: Methodsmentioning
confidence: 99%
“…They were unable to promote osteoclast differentiation,although they exerted a strong chemotactic effect on osteoclast precursors (47). Tenascin C (48) and other biomarkers (49) were identified as predictors of aggressive behaviour. The best treatment of giant cell tumor of the sacrum is controversial.…”
Section: Bone Tumoursmentioning
confidence: 99%